Names of albums and songs of Boris Grebenshchikov - Ерёмин, Евгений (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The article is dedicated to a study of interiorization strategies of the biblical texts in the rock poetry by Grebenshchikov (based on the Book of Songs BG, Moscow 2006). This reveals Grebenshchikov’s specific strategies of the interiorization of an “alien” word. Through the “alien” word in poetry, the author studies Grebenshchikov’s model of the world and reveals the creativity of BG.